Tempo tecnico. La ragione produttiva frana nell’eterno ritorno - Matano, Luca (Mechane, 2022)
The article bases its structure on a fundamental Heideggerian insight: the interaction between man and the world, and thus man’s conception of himself and of things, is what is called ‘technique’, which is thus not reduced to the mere material meaning of producing objects, but taken as mode of being-in-the-world itself. Starting with the Greco-ancient techne, in fact, the way in which man brings things into presence reflects the way in which they come into presence before him: as causes are given around him, so he chooses to cause them. The crux of this basic insight is then as follows: if in the causal attitude the conception of being is given, then current Western technique is nothing more than the result of the sedimentation of Western metaphysical thought from the Athens of Thales to the present day. Our technique is the translation into production and exploitation of the metaphysical dialectic between being and beingness. Certain of this assumption, we move on to analyse ‘metaphysics’ (understood here in the sense of ‘thinking about the being of the being’) in the light of thinking about the essence of time: fuelled by an analysis of the Nietzschean eternal return, the article shows how the essential temporal event (‘the cause’) is really only thinkable, in its essence, in a non-chronological dimension, so as to avoid the classical petitio principii of metaphysics, i.e. thinking about time as if it were also temporally determined. By pursuing the intuition of the instantaneousness of the whole, the ‘summa of contemplation’, one thus frees oneself from blind faith in metaphysical structures by investigating their essence one by one. At this point, on the strength of the two central assumptions, namely the metaphysicality of technique and the essential inconsistency of the metaphysical entity, the question comes to the fore: how does one really let the thought of the essence of the entity in its fundamental instantaneousness act upon man’s technical attitude? In other words: having demonstrated that ‘a thing’ is only a thing as long as it is grasped in its prolongation through a chronological sequence, but that the essence of its being, as of ours, is its being in fieri at every instant, neither a thing nor matter, how can we really let this philosophical consciousness influence the production, purchase, consumption, recycling, use and exploitation of ‘things’? Can the thought of the essence of being exert its influence on the consumerist rhythm of conception and experience of things? Or is it not precisely the consumption of the object, its consideration as a brief function endowed with a certain economic value, the most coherent response to the understanding of its chronological insubstantiality, i.e. its instantaneous essence? Suspecting that current consumerism is not the technical answer to the real consciousness of one’s own existence, the article ultimately asks what philosophical error its ideology stems from, and how one can, in opposition to it, imagine and shape a human existence that respects one’s own essential co-participation in the world.